THE MOTIVATION OF SURABAYA SOCIETY ON SAVING MONEY IN UNIT LINK ASSURANCE ACCOUNT IN PT. PRUDENTIAL LIFE ASSURANCE - Tjiadi, Raymond Kurniawan (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2014)
Personal bankruptcy due to health costs is the concern of Indonesia Government to make sustainable economic condition. This paper emphasizes on the motivation on saving money in insurance products from PT Prudential Life Assurance. The purpose of this study is to identify the peopleâs motivation toward insurance products in Indonesia due to low penetration of insurance market. Informations from field are analyzed based on Vroomâs expectancy theory to break down the human motivation into three elements. The result shows different perceptions between different generations that lead their motivation toward insurance products. The knowledge from this paper serves as the recommendation and help agents from PT Prudential Life Assurance to enhance Indonesianâs motivation on insurance products.